Al-Qur’an Literacy and Islamic Education Among Kkn Students At At-Taqwa Mosque - Sinta Noveliya Windiyansyah; Pahrozi Ahmad; Zerla Nursafitri; Eminia Susila Utami; Tri Eva Lestari (Yayasan Azhar Amanaa Yogyakarta, 2026)
The Community Service Program (KKN) is a form of community engagement that enables university students to apply academic knowledge while contributing to community development. One of the focuses of KKN activities is the enhancement of Qur'anic literacy and Islamic values among children. This program was implemented at At-Taqwa Mosque, Bumi Ayu Village, Selebar District, Bengkulu City, through activities such as Qur'an reading instruction, introduction to hijaiyah letters, learning Qur'anic reading rules, teaching daily prayers, and organizing a Muharram Festival. This study aimed to describe the role of KKN students in improving Qur'anic literacy and Islamic understanding among children at At-Taqwa Mosque. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the program positively contributed to children's ability to recognize hijaiyah letters, understand Qur'anic reading symbols, improve Qur'an reading skills, and memorize daily prayers. In addition, the Muharram Festival, which included short surah memorization, prayer practice, calligraphy coloring, adhan, and Muslim fashion competitions, increased children's enthusiasm, confidence, and participation in religious activities. The program also received strong support from the local community and mosque administrators. Therefore, KKN students played a significant role in strengthening Qur'anic literacy and Islamic values among children while supporting the mosque's function as a center of religious education and community development.